2012
DOI: 10.1128/aem.07869-11
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Traits That Distinguish Neonatal Meningitis-Associated Escherichia coli from Fecal E. coli Isolates of Healthy Human Hosts

Abstract: ABSTRACTNeonatal meningitisEscherichia coli(NMEC) is one of the top causes of neonatal meningitis worldwide. Here, 85 NMEC and 204 fecalE. coliisolates from healthy humans (HFEC) were compared for possession of traits related to virulence, antimicrobial resistance, and plasmid content. This comparison was done to identify traits that typify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
75
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 29 publications
3
75
0
Order By: Relevance
“…The results of this study support the findings of previous studies comparing E. coli strains from cases of meningitis and E. coli strains isolated from other sources (14,15,21). These studies showed that the same sequence types are frequently found in E. coli strains that are isolated from meningitis and other sources, and once further typing schemes are applied, differences can be found.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The results of this study support the findings of previous studies comparing E. coli strains from cases of meningitis and E. coli strains isolated from other sources (14,15,21). These studies showed that the same sequence types are frequently found in E. coli strains that are isolated from meningitis and other sources, and once further typing schemes are applied, differences can be found.…”
Section: Discussionsupporting
confidence: 81%
“…Isolates of E. coli that have caused neonatal meningitis in developed countries have been extensively studied (10,(14)(15)(16)(17)(18)(19). These studies have found that some serotypes and sequence types predominate among the E. coli strains that cause meningitis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We classified as NMEC only those isolates that were positive for both K1 and ibeA. However, in previous human isolate surveys, although around 80% of neonatal meningitis isolates were K1 positive (59)(60)(61), only ϳ30% of K1 isolates were also ibeA positive (59,62,63). It is therefore possible that some K1-positive, ibeA-negative isolates, which here were not considered NMEC, could indeed cause neonatal meningitis by utilizing non-ibeA-related mechanisms (64).…”
Section: Discussionmentioning
confidence: 99%